Kepastian Hukum Aborsi terhadap Korban Pemerkosaan Melalui Proses Pidana - Adhar; Khairunisyah; Ami Hartati Puji Raya; Lalu Kesa Rahmatullah; Fathurrahman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study analyzes the legal certainty of abortion for rape victims within Indonesia’s criminal justice system. The main issue focuses on how abortion exceptions for victims of sexual violence are legally regulated and how the criminal process ensures the protection of victims’ rights both legally and humanely. The research employs a normative legal approach using statutory and conceptual analysis of the Indonesian Criminal Code, Criminal Procedure Code, Health Law, and relevant Government Regulations. The findings indicate that abortion is generally a criminal offense but may be exempted if conducted under medical indication or due to rape, proven through forensic examination and the investigator’s statement. This policy reflects legal protection for victims but faces practical challenges due to the tension between the presumption of innocence and humanitarian needs. The study concludes that a synergistic approach between legal authorities, medical professionals, and psychologists is essential to establish fair and adaptive legal certainty while ensuring victims’ reproductive health rights with dignity.